'A Hazardous Task': Britain and the 1961 Vienna Convention on Diplomatic Relations. Issue 2 (15th March 2017) - Bruns, Kai S.
ABSTRACT: In 2014, the Vienna Convention on Diplomatic Relations celebrated its fiftieth anniversary since its coming into force in 1964. Setting out the privileges and immunities accorded to diplomats and diplomatic missions, the negotiations of this convention were part of the United Nations' plan to strengthen the international rule of law. This article analyses the role of Britain, one of the major actors in the negotiation process. It explores how Britain's negotiation position was shaped by diplomatic realities of the 1950s, and the strategies used to ensure Britain's interests being reflected in the final convention. The focus will be on the overall political pressure that underlined Britain's negotiation position, in order to reveal the general UK position on the codification of diplomatic privileges and immunities. Despite the remarkably friendly atmosphere at the 1961 Vienna conference, Britain could not press through all its amendments which, through the concluding legislation process, protracted Britain's ratification process. The article shows while London was supporting the codification of international law, codification by convention was not its ultimate choice. Therefore, the subsequent legislation process was marked by an inter-departmental dispute between the Foreign Office and Treasury, inter alia, on the exemption of Scotch whisky from excise duties.